2000
DOI: 10.1046/j.1365-8711.2000.03180.x
|View full text |Cite
|
Sign up to set email alerts
|

The star formation histories of low surface brightness galaxies

Abstract: We have performed deep imaging of a diverse sample of 26 low surface brightness galaxies (LSBGs) in the optical and the near-infrared. Using stellar population synthesis models, we find that it is possible to place constraints on the ratio of young to old stars (which we parameterise in terms of the average age of the galaxy), as well as the metallicity of the galaxy, using optical and near-infrared colours. LSBGs have a wide range of morphologies and stellar populations, ranging from older, high metallicity e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
89
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 46 publications
12
89
1
Order By: Relevance
“…However, even then, the amount of reddening due to dust will be insufficient to explain the large radial color gradients now observed in a number of LSB galaxies (de Blok, van der Hulst, & Bothun 1995 ;MGvD99 ;Matthews et al 2000 ;Bell et al 2000). Thus some LSB galaxies must have large intrinsic stellar population and/or metallicity gradients in their disks.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…However, even then, the amount of reddening due to dust will be insufficient to explain the large radial color gradients now observed in a number of LSB galaxies (de Blok, van der Hulst, & Bothun 1995 ;MGvD99 ;Matthews et al 2000 ;Bell et al 2000). Thus some LSB galaxies must have large intrinsic stellar population and/or metallicity gradients in their disks.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, using a simple foreground screen model, MGvD99 suggested that in the case of UGC 7321, dust reddening could not explain more than D0.2 mag of the observed B[R color gradient. Using both foreground screen and Triplex dust models (see Disney, Davies, & Phillipps 1989), Bell et al (2000) argued that the amount of dust reddening needed to produce the observed color gradients in their sample of less inclined LSB galaxies was also too large to be consistent with observations.…”
Section: Color Gradients In Ugc 7321mentioning
confidence: 96%
See 3 more Smart Citations